The emigrants - Sebald, W. G. (Winfried Georg) 1944-2001; Hulse, Michael 1955- (New York New Directions, 1996)
The road to exile of four men. One is a teacher, fired by the Nazis from his job for having a Jewish ancestor, then inducted into the German army. Of the others, all Jews, one is a surgeon who commits suicide as he is unable to assimilate into British society, a second is an artist, a third becomes a butler in New York.
Keywords: Exiles -- Fiction; World War, 1939-1945 -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Historical fiction; Jewish fiction